Joint strategic and tactical planning under the dynamics of a cap-and-trade scheme. Issue 12 (2016) - García-Alvarado, M.; Paquet, M.; Chaabane, A.
Abstract: This paper explores how environmental investments, capacity expansion and production and inventory planning interact to comply with a cap-and-trade mechanism. We consider a supply chain system subject to a cap-and-trade regulation. Demand may be met by two production technologies: low-carbon and conventional. The former uses recovered products and is considered greener, but highly expensive. Further, its capacity can be increased throughout the planning horizon. It is also possible to cut the total carbon footprint by investments in emission control technologies. Decisions are then made on how best to invest in carbon abatement strategies, capacity sizing, and production and carbon management planning to meet a cap-and-trade scheme over time. We modeled the system as a mixed integer linear problem. To illustrate the applicability of our approach, we focused on the pulp and paper industry. We characterize strategic and tactical decisions and perform a sensitivity analysis to determine the importance of allowance prices and freely granted emissions. Our findings support the potential of aligned strategic and tactical plans under environmental policies. In particular, our results show if the allowance price is beyond a threshold value, investments are critical to the economic survival of a firm.